Faktor-Faktor Yang Mempengaruhi Terjadinya Phlebitis Di Rumah Sakit Bakti Timah Karimun - Rozy Fitriana; Elvi Murniasih; Yulianti Wulandari (Jurnal Ilmiah Kedokteran dan Kesehatan, 2024)
Phlebitis is vein inflammation caused by chemical or mechanical irritation. The achievement of Phlebitis rates at Bakti Timah Karimun Hospital in the last three months from October to December 2022 exceeds the tolerable standard. to find out the factors that influence the occurrence of Phlebitis. Analytical survey design with a cross sectional approach and sampling technique using purposive sampling with a sample size of 30 patients. Research data was collected through observation methods. The research results were analyzed univariately and bivariately with chi square. The factors that influence the occurrence of phlebitis are age > 60 years (13.3%), female gender (13.3%), comorbidities (10%), duration of infusion > 3 days (10%), location of installation infusion in the cephalic vein (10%) and hypertonic infusion fluid (10%). The results of the bivariate analysis showed a significant relationship between the 6 factors assessed (age, gender, comorbidities, duration of infusion, location of infusion and type of fluid used), namely with a p value <0.05. All the factors assessed show the potential to cause phlebitis and there is a significant relationship between the factors assessed and the incidence of phlebitis. It is hoped that if factors are found that have the potential to cause phlebitis, phlebitis prevention can be implemented in accordance with the SOP in the hospital.